2019
DOI: 10.37868/sei.v1i1.36
|View full text |Cite
|
Sign up to set email alerts
|

DoS and DDoS vulnerability of IoT: A review

Abstract: Internet of Things (IoT) paradigm became particularly popular in the last couple of years in such a way that the devices are present in almost every home across the globe. Using cheap components one can connect any device to the internet and enable information collecting from the environment, making everyday life a lot easier. Even though it does bring multiple advantages to the table, at the same time it brings certain challenges and vulnerabilities that need to be addressed. In this paper we focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…With these added new components, a vehicle represents as an intelligent vehicle which supports many services. The authors in [ 2 , 11 – 18 ] introduce vehicle as a resource (VaaR) which adopted various vehicular potential services. According [ 3 , 4 , 6 , 19 ] to authors' point of view, the vehicle can provide various instances of VaaR.…”
Section: Previous Studymentioning
confidence: 99%
See 1 more Smart Citation
“…With these added new components, a vehicle represents as an intelligent vehicle which supports many services. The authors in [ 2 , 11 – 18 ] introduce vehicle as a resource (VaaR) which adopted various vehicular potential services. According [ 3 , 4 , 6 , 19 ] to authors' point of view, the vehicle can provide various instances of VaaR.…”
Section: Previous Studymentioning
confidence: 99%
“…The components of each layer have distinct task and their locations so the role of them is different as well. The system suggested that the wireless communication technology dedicated shorted-range communications [ 2 – 4 , 11 , 18 , 19 ] is a medium between any two layers with one-hop distance separating them.…”
Section: Model Of a Networkmentioning
confidence: 99%
“…Many three-dimensional chaotic systems' ideas may be found in [1][2][3][4]. e first four-dimensional model (4D) was proposed in 1979 and provided a system with two positive LYP formulas and real variables; since then, numerous 4D chaotic schemes have been identified in [5,6]. e size of a HYCH system is proportional to the number of positive LYP chaotic system architectures which is four [7].…”
Section: Introductionmentioning
confidence: 99%
“…where (u 1 (s), to, u 6 (s)) T ∈ R 6 . Tiny changes in the starting values cause small variances in the sheer randomness of chaotic complex systems, according to this multidisciplinary hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…IoT devices equipped with embedded controllers are often targeted by denial-of-service attacks. Denialof-service (DoS) attacks and Distributed Denial-of-Service (DDoS) attacks are the most common attacks on the Internet of Things [59]. They can take many forms and are defined as attacks that can undermine the network's ability to perform its function.…”
Section: Switched Systemsmentioning
confidence: 99%